Feasibility of telepsychology support for patients with advanced cardiorespiratory diseases and their caregivers - Gazzi, Lidia; Comini, Laura; Scalvini, Simonetta; Taccolini, Irene; Vitacca, Michele (Frontiers in Psychology, 2022)
Objective: To test the feasibility of telepsychology support for patients with severe cardiorespiratory disease and their caregivers. A secondary objective was to explore pre-post relationships between patients’ and caregivers’ clinical measures. Methods: A telehealth program incorporating telepsychology support, i.e. an “on-demand” phone service with a psychologist, was provided to consecutive cardiorespiratory patients at discharge from inpatient rehabilitation and to their caregivers. At the start and end of the 1-year program, participants were interviewed “face-to-face” and anxiety/depression level, patients’ quality of life (MRF 26, SF-36, and MQOL), and caregivers’ (n=18) family strain (FSQ) and needs (CNA) were assessed: we analysed the correlations, and evaluated customer satisfaction. Results: Of 80 eligible individuals, 40 took part in the study: 22 patients (FVC=39±14%; EF=39±13%) and 18 caregivers. Eleven (28%, 6 patients and 5 caregivers) requested tele-psychological support, resulting in 51 consultations focused on anxiety, difficulty in patient management, worry about the patient’s emotional state, and need for emotional support; 3 participants underwent a tailored psychotherapy program. All participants expressed high satisfaction with the service. At enrolment, anxiety was less evident in patients (73% males) than in caregivers, while depressive symptoms were more evident (6.5±3.1), and this correlated with MRF 26 and MQOL. Caregivers’ (94% females) FSQ showed a “strongly recommended” need for support; at enrolment, high levels of anxiety/depression were correlated to high FSQ (for both, p<0.05); depressive symptoms correlated negatively with age (p=0.025) and positively with emotional needs (p=0.025); anxiety was positively correlated with education level (p=0.048). At follow-up, patients’ perception of support (n=13/22) tended to increase (p=0.089), while caregivers’ strain (n= 10/18) tended to decline (to within the “range of attention”). At enrolment, caregivers’ anxiety/depression and strain correlated with patients’ quality of life (for both; p<0.05). At follow-up, caregivers' strain correlated with patients’ quality of life (p=0.028) and cognitive performance (p=0.048). Conclusion: Telepsychology support associated with a telehealth service is feasible and satisfying for both participants and psychological management. A suitable support program can benefit both patients and caregivers, particularly those at higher risk of depressive symptoms (younger caregivers) and anxiety (all caregivers).